Pemberdayaan Masyarakat Berbasis Teknologi Melalui Penerapan Mesin Reverse Osmosis (RO) pada Usaha Depot Air Isi Ulang BUMDesa Unggul Sari - Jefri Lianda; Hikmatul Amri; Adrian Irnanda Pratama; Nurul Huda; Muhammad Fajar; Mohd. Raihan Helmi (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to empower the community through the introduction of PDAM water treatment technology into suitable water for consumption in the form of applying Reverse Osmosis (RO) 200 GDP to BUM refill water depot businesses in Unggul Sari Village, Wonosari Village, Bengkalis Regency. The method of implementing this service used participatory training and mentoring. Evaluation of this service used was the Community Service Management standard listed in Permenristekdikti Number 44 of 2015. This community service activity resulted in the realization of a BUM Unggul Sari Village BUM refill water depot business, Wonosari Village, with a refillable water production capacity of 65 gallons per day. In addition, partners could operate technology with a Reverse Osmosis membrane system.Â Â